Factors influencing music preferences among diploma of music students in UiTM Shah Alam / Putera Rushdun Kamil Alifi Fikri Abdul Rasid and Syamim Sawalludin - Abdul Rasid, Putera Rushdun Kamil Alifi Fikri; Sawalludin, Syamim (2019)
Music preference refers to the psychological factors behind peoples' different music preferences. Music is heard by people daily in many parts of the world and affects people in various ways from emotion regulation to cognitive development, along with providing a means for self-expression. The purpose of this study are to investigate the music preferences among diploma music students and to find out the music preferences among diploma music students according to gender. The sample for this study are 50 respondents of diploma students (n=50) from the Faculty of Music, UiTM Shah Alam.